Modified Dietetic Skim And Cotton Sheet Oil Dan Susu Formula 75 Terhadap Berat Badan Anak Balita Gizi Kurang - Pembronia Nona Fembi; Yosefina Nelista (Poltekkes Kemenkes Medan, 2021)
Children under five are a group that is prone to malnutrition because they are still experiencing a growth cycle, a development that requires more nutrients than other age groups. The impact of nutritional deficiencies; low body resistance, the body is susceptible to infectious diseases. The purpose of this study was to analyze the effectiveness of giving modified dietetic skim and cotton sheet oil (MODISCO) and Formula-75 milk to increase body weight of malnourished children in Puskesmas Waigete, Sikka Regency. The type of research used is Quasy experimental pretest and posttest design. The population of this research was 181 underweight children with malnutrition. The sampling technique used purposive sampling. The sample of this study was 24 underweight children with malnutrition, divided into 2 (two), namely group A was given MODISCO intervention and group B was given Formula-75 milk. The intervention was given once a day for 1 month at a dose of 150 kcal / kgbb / day for MODISCO and 1000 ml per day for 75 formula milk. Data analysis used Paired t-Test and Independent Samples Test. Paired T-Test analysis, groups A and B obtained P-value (0.000) <0.05, it was concluded that there was an increase in body weight after being given MODISCO and Formula-75 milk. Based on the analysis of the Independent Samples Test, groups A and B obtained a P-value (0.876)> 0.05, it was concluded that there was no difference in body weight for under-nourished toddlers who were given MODISCO and Formula-75 milk. There is no difference in body weight of malnourished underweight children in group A and group B, so it is concluded that MODISCO and Formula-75 milk can increase the weight of malnourished children underweight. The results of this study are an additional intervention to increase the weight of children under malnutrition.